The Making of the Humanities Volume II: From Early Modern to Modern Disciplines - Bod, Rens; Maat, Jaap; Weststeijn, Thijs (Amsterdam University Press, 2012)
While it is clear that around 1800 the humanities as a discipline rose to prominence, it is less clear what the exact nature of this shift in academia was. Was it a sudden revolution caused by a momentary but powerful change in the zeitgeist or the turning point of a much longer process? In this volume, the editors have selected a series of essays that look at the origins of the humanities and find that long before 1800 the concept of the humanities was already at the fore. The shift around 1800 was thus mostly institutional, not theoretical. The Making of the Humanities traces this new finding through a broad range of disciplines including literary theory, linguistics, art history, and musicology.